COMPARISON OF TOTAL ANTIOXIDANT SERUM LEVEL IN POSITIVE AND NEGATIVE H. PYLORI GASTRITIS PATIENTS - Donny P Lubis, Gontar A Siregar & Taufik Sungkar (International Journal of Research Science and Management, 2019)
Gastritis is an inflammatory of stomach that can occur either acutely or gradually as a chronic condition. Incidence of gastritis in Indonesia is high, which is 274,396 cases out of 238,452,952 inhabitants. One of the most common causes of gastritis is Helicobacter pylori (H. pylori).Gastric mucosa damage can be caused by Reactive Oxygen Species (ROS) which stimulated by H. pylori. Cells are protected against the harmful effects of ROS by antioxidant enzymes and other non-enzymatic antioxidants, so that the amount of antioxidant and free radicals in the body can be balanced. There were 40 samples obtained through consecutive sampling in March-July 2018. Gastritis was ensured by endoscopy (Olympus, Tokyo, Japan). H.pylori is established through a change in color from yellow to red, magenta, pink, or orange in the examination of Campylobacter Like Organism test (CLO). Total antioxidants level examination using a serum total antioxidant kit with the ELISA method (kit Randox Total Antioxidant, Cat. No. NX 2331, Randox Laboratories Ltd, UK). Data were collected and analyzed using SPSS version 22. There was significant association between level of total antioxidant serum and gastritis due toH. pylori infection with p value p = 0.004.